1996
DOI: 10.1073/pnas.93.26.15364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age onin vivorates of mitochondrial protein synthesis in human skeletal muscle

Abstract: A progressive decline in muscle performance in the rapidly expanding aging population is causing a dramatic increase in disability and health care costs. A decrease in muscle endurance capacity due to mitochondrial decay likely contributes to this decline in muscle performance. We developed a novel stable isotope technique to measure in vivo rates of mitochondrial protein synthesis in human skeletal muscle using needle biopsy samples and applied this technique to elucidate a potential mechanism for the age-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
393
5
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(435 citation statements)
references
References 39 publications
25
393
5
7
Order By: Relevance
“…3). The highest FSR were seen in mitochondrial protein and again decreased with age (Rooyackers et al 1996a), while the FSR of a cytosolic muscle protein fraction was intermediate and did not change with age (Fig. 3).…”
Section: Amino Acid Incorporation Methods To Measure Protein Synthesimentioning
confidence: 87%
See 1 more Smart Citation
“…3). The highest FSR were seen in mitochondrial protein and again decreased with age (Rooyackers et al 1996a), while the FSR of a cytosolic muscle protein fraction was intermediate and did not change with age (Fig. 3).…”
Section: Amino Acid Incorporation Methods To Measure Protein Synthesimentioning
confidence: 87%
“…Mean values were significantly different from those for the youngest age-group (mean 24 years): *P < 0·05. Summary of data published by Rooyackers et al (1996a) and Balagopal et al (1997).…”
Section: Amino Acid Incorporation Methods To Measure Protein Synthesimentioning
confidence: 99%
“…In general, the glycolytic capacity of skeletal muscle is maintained with age (Rogers & Evans, 1993). In contrast, the activity of enzymes involved in oxidative metabolism (eg succinate dehydrogenase; citrate synthase; cytochrome c oxidase) and b-oxidation of fatty acids (eg H 3-hydroxyacyl-CoA dehydrogenase) are reduced with age (Coggan et al, 1992a, b;Rooyackers et al, 1996). These enzymatic changes would have the net effect of decreasing fat oxidation relative to glucose oxidation and may partially explain the reduction in exercising fat oxidation observed in older individuals (Sial et al, 1996).…”
Section: Oxidative Capacity Of Fat-free Massmentioning
confidence: 99%
“…Although a number of previous studies have reported a reduction in the fractional synthetic rate of mixed muscle and specific myofibrillar proteins with age,3, 24, 25 these studies were performed on muscle biopsies from human subjects. Moreover, most of the biopsies were from muscles such as the quadriceps femoris and vastus lateralis that consist of a mixture of fast‐twitch and slow‐twitch fibres and until recently, it was impossible to separate the fractional synthesis rate of the various fibre types 23.…”
Section: Discussionmentioning
confidence: 99%